Addiction and Recovery in Dutch Governmental and Practice-Level Drug Policy: What's the Problem Represented to be?. (October 2022) - Martinelli, Thomas F.; Vander Laenen, Freya; Nagelhout, Gera E.; van de Mheen, Dike H.
Around 2009, 'recovery' was introduced in the Netherlands as a new approach to drug addiction and addiction services. Recovery is now featured in practice-level policy but is absent in governmental drug policy. To investigate whether the Dutch recovery vision is coherent with governmental drug policy, we apply Bacchi's What's the problem represented to be? approach to analyse problematizations of 'drug addiction'. We analysed two influential practice-level policy documents and one governmental drug policy document. We found that governmental policy addresses the harms and public nuisance of drug addiction, whilst practice-level policy addresses the wellbeing of persons with addiction. Despite these different starting points, the Dutch recovery vision seems coherent with both problematizations. Its adoption in the Netherlands was less subject to political debate compared to other countries. This may be a result of recovery being driven by bottom-up efforts without government intervention, leading to constructive ambiguity between government- and practice-level policies.